Some morphological features of order documents in the Uzbek language - Shodiyeva Mehribon Fakhriddin qizi (Zien Journals, 2022)
This article analyzes the types of documents that form the basis of order documents morphologically. In particular, morphological units in the text of documents such as orders and directives are studied.
Keywords: command documents; command; order; decision